Effect of Removing the Leaves and Awns on Grain Yield and Yield Components of Two Varities of the Barley (Hordeum vulgare L.) Under The Conditions Of Tripoli Region- Libya (Albayan Scientific Journal, 2023)
This experiment was conducted with a research station faculty of agriculture, Tripoli University ,Libya to study effect of removing the leaves and awns on grain yield and yield components of two varieties of the barley during 2011/2012 growing season ,A split plot design in three replications was applied,where the main plot included the two varietrs of  barley(Wadi Autba) Local Var. and (Vestito)  Italian cultivar, while the sub-plots included removal treatments (control, remove all leaves , remove the flag leaf, remove the flag leaf and awn ,remove the awn ).The results have shown significant differences in grain yield with respect to different treatments. The removal of flag leaf,awns, and a combination of flag and awn decreases the grain yield by 40,39, and 49% respectively when compared with control treatment. The results also showed that the average 1000-grain weight decreased significantly by 6.87 and 9.75 gram when awns, and flag leaf and awn removed respectively. It is recommended from results of this study to use awned varieties and keep leaves intact since they are the main sources of producing carbohydrates through the process of photosynthesis.
Keywords: Barley-Leaf Removal; Awn removal; Grain yield; Yield compenent